Preliminary evaluation of a dual chamber pacemaker with bradycardia diagnostic functions. - Lascault G; Barnays C; Cazeau S; Frank R; Medvedowsky JL (Pacing & Clinical Electrophysiology, 1995)
Unexplained Syncope is the main indication for the implantation of a diagnostic pacemaker. Studies on those implanted have shown that in patients with unexplained syncope, the diagnosis of paroxysmal bradycardia was feasible and reliable. The present study was designed to evaluate a new bradycardia diagnosis algorithm, loaded in a dual chamber pacemaker, in 24 patients considered as candidates for diagnostic pacemakers. During a mean follow-up of 253 days, at least one bradycardia episode was recorded in 13 patients. The mean number of detected bradycardias was 6 and the median was 3. The mean delay between the algorithm activation and the first bradycardia episode was 67 days. The mechanism of bradycardia was atrioventricular block in 6 patients, sin us node dysfunction in 6 patients, and consecutive blocked atrial premature beats in 2 patient, as indicated by the event markers. In 11 patients bradycardia was recorded during the daytime only or day and night. In two patients the episodes were recorded only at night. Overall, the algorithms was well-tolerated; however, some mild symptoms were observed due to the method of bradycardia determination, allowing bradycardia. Three patients were symptomatic as a direct result of the algorithm operation, and four patients had symptoms related to the single chamber operation of the pacemaker while functioning in the diagnosis mode (VDI). These symptoms were relieved with DDD pacing.